ANALYTICAL HIERARCHY PROCESS (AHP) APPROACH ON CONSUMER PREFERENCES OF RESEDENTIAL HOUSING IN GATED COMMUNITY MANADO - Wangke, Shinta (Universitas Sam Ratulangi, 2014)
Construction growth for the residential property in gated community Manado had reached its highest growth of 7,68% in Q2 2014. Increasing purchase intention of the house buyers resulted huge increase in the residential housing price in gated community. Since the gated community started to become a trend as a preferred choice for people to stay in, therefore, this study seeks to discover the reason for people to purchase residential properties.